Pendampingan Siswa Taman Kanak-Kanak AnubanJitjongrak School, Thailand, dalam Lomba Edukatif di Chokchai Krabi School, Thailand - Nailah, Khalisha Ana; Rohim, Abdul; Anggraini, Nori (Abdimas Universal, 2026)
This community service activity aims to describe the implementation of student assistance for kindergarten students of AnubanJitjongrak School, Thailand, in participating in educational competitions at Chokchai Krabi School, Thailand, and to analyze its contribution to students’ learning experiences. The educational competitions included clay handicraft, coloring, and paper collage activities. This study employed a descriptive qualitative approach involving seven kindergarten students. Data were collected through participatory observation during the competition, semi-structured interviews with accompanying teachers, and activity documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that student assistance in educational competitions contributed positively to the development of creativity, fine motor skills, self-confidence, and social abilities. Students demonstrated high enthusiasm, active participation, and the ability to complete tasks according to the given instructions. Furthermore, assistance provided by teachers and student mentors helped students adapt to a new learning environment and created a positive and enjoyable competitive atmosphere. Therefore, assistance in educational competitions can be considered an effective form of non-formal learning that supports holistic development in early childhood education.